Large genetic diversity for fine-flavor traits unveiled in cacao (Theobroma cacao L.) with special attention to the native Chuncho variety in Cusco, Peru - Eskes, A.; Rodríguez, C.A.C.; Cruz Condori, D.; Seguine, E.; García Carrion, L.; Lachenaud, P. (Agrotropica, 2018)
The fine-flavor cocoa industry explores mainly six chocolate sensory traits from four traditional cocoa (Theobroma cacao L.) varieties. The importance of cocoa pulp flavors and aromas has been ignored until we recently showed that they migrate into beans and into chocolates. Pulp sensory traits are strongly genotype dependent and correlated to human preference. Growers of the native Chuncho variety from Cusco, Peru, which is the cocoa that the Incas consumed, make pulp juices from preferred trees (genotypes). Evaluations of 226 preferred trees evidenced presence of 64 unique mostly multi-trait sensory profiles. Twenty nine of the 40 flavors and aromas identified mimic those of known fruit and flower or spice species such as mandarin, soursop, custard apple, cranberry, peach, banana, inga, mango, nut, mint, cinnamon, jasmine, rose and lily. Such large sensory diversity and mimicry is unknown in other commercial fleshy fruit species. So far, 14 Chuncho-like pulp sensory traits have been identified among different cocoa varieties elsewhere suggesting that Chuncho is part of the ¿centre of origin¿ for cocoa flavors and aromas. Stable expression of multi-trait Chuncho sensory profiles suggest pleiotropic dominant inheritance, favoring selection for quality traits, which is contrasting with the complex sensory trait determination in other fleshy fruit species. It is inferred that the large sensory diversity of Chuncho cocoa can only be explained by highly specialized sensory trait selection pressure exerted by frugivores, during evolution, and by the indigenous ¿Matsigenkas¿, during domestication. Chuncho beans, still largely employed as a bulk cocoa source, deserve to become fully processed as an extra-fine cocoa variety. The valorization of the numerous T. cacao sensory profiles in chocolates, raw beans and juices should substantially diversify and boost the fineflavor cocoa industry, this time based on the Matsigenka/Inca and not anymore on the Maya cocoa traditions.